Implementation of Family Planning Village as an Effort to Prevent Stunting among Children Under Five - Rahmuniyati, Merita Eka; Sahayati, Sri (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2023)
Background: The prevalence of stunting in Yogyakarta City in 2022 has been successfully reduced to 13.8%. This figure is lower than the national prevalence of stunting, which is 21.6%. The success of reducing stunting is supported by the KB Village program. The research aims to explore the implementation of Family Planning Villages as an effort to prevent stunting in toddlers.Method: This research uses a qualitative approach. This research was carried out in the KB Village, Purwobinangun Village, Pakem Community Health Center Working Area in October – November 2022. Participants in this research were family planning instructors, health cadres, head of the KB Village, Nutritionist. In-depth interview technique was used for data collection. Data analysis was carried out in stages: data collection, data reduction, data presentation, drawing conclusions.Results: Efforts to prevent stunting in the KB Village area can be carried out by implementing various stunting prevention activities, such as providing education to the community and providing additional food to stunted toddlers, caring for children through the role of fathers. Encourage cooperation and collaboration across sectors and activity groups. There are obstacles such as not being able to maximize the activities of the Youth Information and Counseling Center (PIK-R) and online reporting due to limited human resources.Conclusion: The implementation of KB Villages in efforts to prevent stunting has gone well through cross-sectoral collaboration.